(3LhGH eSCdI Sdhc WQjb GdUhajIs
(3ChdgG (B:s
(3GdMeO ddg hMOg CeG HYO abO HdZfi cJGHce hJYQaJ efg eG WdHJe hbO JUaMJ cd hGMO ef GdcJGHjf s
(3BNQgG (B:s
(3hgPG GdbOQ ef GdcdGe GdeNJUQ cGma ai Jbjje eG jPcQg GdTjN QVi Gddg Yfg ef GdcdGe GdeQhi Yfg hHGddg GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGdP s
Keywords: (3GdJUha hGdBOGH GdTQYjIs